Appendicitis complicated by appendiceal metastasis via peritoneal dissemination from lung cancer. Issue 4 (5th May 2016) - Shiota, Naoki; Furonaka, Makoto; Kikutani, Kazuya; Haji, Keiko; Fujisaki, Seiji; Nishida, Toshihiro
Abstract: Peritoneal disseminations from lung cancer are difficult to detect during the patient's clinical course. Therefore, complications of this condition are unclear. We report a case in which peritoneal dissemination from lung cancer complicated appendicitis. A 74‐year‐old man with lung cancer who was receiving maintenance therapy presented at our hospital because of abdominal pain. It was the seventh day after the 14th cycle of maintenance therapy with bevacizumab. He was diagnosed with acute appendicitis. The resected appendix showed acute appendicitis complicated by appendiceal metastasis from lung cancer. Adenocarcinoma was observed predominantly in the serous membrane from the neck to the tail of the appendix. The distribution of the adenocarcinoma was diffuse. Peritoneal dissemination was considered the route of metastasis. He was admitted to the palliative care unit 10 months after appendectomy. Appendiceal metastasis via peritoneal dissemination from lung cancer complicated appendicitis in our patient who had been receiving bevacizumab. Abstract : Peritoneal dissemination from lung cancer complicated appendicitis. Lung cancer metastasis slowly progressed receiving maintenance therapy with bevacizumab.